2021
DOI: 10.1002/edm2.251
|View full text |Cite
|
Sign up to set email alerts
|

Complete blood counts with red blood cell determinants associate with reduced beta‐cell function in seroconverted Swedish TEDDY children

Abstract: Objectives: To investigate whether changes in complete blood count (CBC) in islet autoantibody positive children with increased genetic risk for type 1 diabetes are associated with oral glucose tolerance tests (OGTT) and HbA1c over time. Methods:The Environmental Determinants of Diabetes in the Young (TEDDY) study follows children with increased risk for type 1 diabetes in the United States, Germany, Sweden and Finland. In the current study, 89 Swedish TEDDY children (median age 8.8 years) positive for one or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
(82 reference statements)
2
4
1
Order By: Relevance
“…Therefore, it might be speculated that innate increasing of beta-cell secretion, may be an underlying factor for erythrocyte metabolism. However, unlike our study, Salami et al found decreased levels of RDW were associated with increased fasting insulin among islet autoantibody positive children with increasing risk for type 1 diabetes [ 9 ]. On the other hand, some of the patients in our study were treated with exogenous insulin which might affect erythropoiesis.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, it might be speculated that innate increasing of beta-cell secretion, may be an underlying factor for erythrocyte metabolism. However, unlike our study, Salami et al found decreased levels of RDW were associated with increased fasting insulin among islet autoantibody positive children with increasing risk for type 1 diabetes [ 9 ]. On the other hand, some of the patients in our study were treated with exogenous insulin which might affect erythropoiesis.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies pointed that an increase in RDW level has been shown to be closely related to T2DM or its complications and a marker of worsening diabetes control [ 6 – 8 ]. A reduction in counts of red blood cells and levels of haemoglobin in Swedish TEDDY children with multiple islet autoantibodies has been shown, and RDW values are significantly associated with HOMA-β and HbA1c[ 9 ].However, there are currently little clinical research on the correlation between red blood cell distribution and islet β-cell function among patients with LADA. Considering the importance of patients with LADA, the purpose of this study was to investigate the relationship between RDW and islet β-cell function in patients with LADA.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to lymphocyte counts, neutrophil count had an inverse association with T1D risk and displayed a negative genome-wide genetic correlation with T1D, albeit statistically insignificant. Clinical observations have documented reduced lymphocyte and neutrophil counts in patients with of T1D [1619, 37]. Our findings thus suggest that these altered counts could contribute to disease.…”
Section: Discussionsupporting
confidence: 54%
“…In line with this hypothesis, clinical observations have documented altered leukocyte counts that correlate with the progression of T1D [1619] and CAD [20]. In particular, the counts of neutrophils, which constitute the bulk of circulating leukocytes and are short-lived, requiring continuous replenishment by hematopoiesis [21], are consistently diminished in genetically at-risk individuals for T1D and in those diagnosed with the disease [1619]. However, it is unknown whether these altered leukocyte counts causally contributes to disease and the co-occurrence of T1D and CAD, or these altered leukocyte counts are simply a consequence of disease.…”
Section: Introductionmentioning
confidence: 90%
“…This HbA1c increase is still within normoglycemic ranges detected up to years before onset. We have previously shown in autoantibody positive TEDDY children an inverse association of mean corpuscular hemoglobin (MCH) and mean corpuscular volume (MCV) with HbA1c, 23 indicating a decrease in iron levels generally caused by an aberrant erythropoiesis or a reduction in iron intake or absorption. 24 , 25 Thus, further research is required to clarify whether there are common factors associated with erythropoiesis and development of type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%